A grounded theory study on motivational development after detours in young adulthood: How extra-vocational training affects aspirations - Monique Landberg; Peter Noack (International Journal for Research in Vocational Education and Training (IJRVET), 2022)
Context: In the present study, we explore what motivates young adults to re-engage with education or employment after a period of non-engagement. Insights into this process facilitate the implementation of tailored support measures for at-risk groups. It is well-known that young people who are not involved in any kind of education, employment, or training face further risks to their professional and psychological development.~Methods: Using a grounded theory approach, interviews with young adults from various educational tracks were analyzed, compared, and contrasted. The sample was focused mainly on apprentices in extra-vocational training and professionals working with young people to describe the process of re-engaging in detail (n = 30).~Findings: Our analyses suggested that frustrating prior experiences and offers to participate in government-funded vocational training prompted motivation to learn an occupational skillset. Undergoing an apprenticeship enabled young adults to develop the motivation to finish vocational training and to plan on further education.Conclusion: The implications of these results as they pertain to Germany's labor market policies, which foster a sense of individual responsibility to facilitate the achievement of professional success, are discussed. Furthermore, the implications for supporting further educational aspirations when working with young adults are discussed.
Keywords: 330; Access to Education; At-Risk Youth; Apprentice; Career Pattern; Educationally Disadvantaged Youth; Vocational Education and Training; VET